Pengaruh Corporate Social Responsibility (CSR) dan Leverage Terhadap Kebijakan Dividen dengan Ukuran Perusahaan Sebagai Variabel Moderasi - Andini Novita; Wiwik Lestari; Linda Purnama Sari (Journal of Business & Banking, 2025)
ABSTRACT This study aims to examine the effect of Corporate Social Responsibility (CSR) disclosure and leverage on corporate dividend policy. Dividend policy is treated as the dependent variable and is proxied by the dividend payout ratio and dividend to sales. The independent variables are CSR disclosure, measured using the CSR Score, and leverage, measured by the debt-to-asset ratio. This study also employs firm size as a moderating variable, measured by the natural logarithm of total assets. The population consists of companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period, selected using a purposive sampling method. The study uses 92 observations as the sample. The data used are secondary data obtained from companies’ annual reports and sustainability reports. This research adopts a quantitative approach using panel data regression analysis. The results show that CSR disclosure has a positive and significant effect on the dividend payout ratio but does not have a positive effect on dividend to sales. Leverage has a negative and significant effect on dividend policy, both when proxied by the dividend payout ratio and dividend to sales. Furthermore, the moderating role of firm size in the relationship between CSR disclosure and dividend policy shows insignificant results when dividend policy is proxied by the dividend payout ratio, but shows a strengthening and significant effect when proxied by dividend to sales. The theoretical implication of this study supports stakeholder theory, which suggests that companies are not only responsible to shareholders but also to all stakeholders.